A brief overview of the national outbreak of e-cigarette, or vaping, product use ─associated lung injury (EVALI) and the primary causes (2020)
For the purpose of public health surveillance, cases are defined by a history of e-cigarette, or vaping, use within 90 days prior to symptom onset, pulmonary infiltrates on chest imaging, and the absence of infectious or other alternative diagnoses. [2] EVALI cases were first reported to CDC in August 2019. National emergency department data and active case reporting from state health departments around the country show a sharp rise in symptoms or cases of EVALI in June 2019, a peak in September 2019, and a gradual, but persistent decline since then. Although cases related to the outbreak have decreased, new cases continued to be reported to CDC by state health departments and samples connected to EVALI patients continued to be tested by both CDC and FDA through February 2020 when systematic reporting to CDC ceased because of the decline in the epidemic. [4-6] However, some states have continued to identify cases and clinicians should remain vigilant in identifying and treating patients who may have EVALI. [7]